High level Antarctic EIA under the Madrid Protocol: state practice and the effectiveness of the Comprehensive - Hemmings, AD; Kriwoken, LK (International Environmental Agreements: Politics, Law and Economics, 2010)
The 1991 Protocol on Environmental Protection to the Antarctic Treaty(Madrid Protocol), the latest instrument of the Antarctic Treaty system (ATS), establishesenvironmental standards to manage 10% of the planet. Under the Madrid Protocol, allactivities subject to advance notice reporting obligations under the 1959 Antarctic Treatyare required to undergo prior Environmental Impact Assessment (EIA). The highest levelEIAtermed a Comprehensive Environmental Evaluation (CEE)requires internationalscrutiny. This is the only form of EIA where such scrutiny occurs and the only contextunder the Madrid Protocol or any other part of the ATS where the proposed actions of StateParties, or operators subject to their jurisdiction, are subject to formal international review.Whilst this review does not provide a veto, it has been viewed as an important developmentin the Antarctic multilateral regime. To date, there have been 19 CEEs. This article reviewsthe Antarctic CEE process and evaluates its application in practice against the environmentalobligations established in the Protocol. Whilst most CEEs are substantial documentsand processes, which have raised the standard of environmental care in the area,there are significant generic limitations. Not one CEE appears to have led to substantialmodification of the activity as first elaborated by the proponent, let alone a decision not toproceed with the activity, despite this being a mandatory consideration. There are indicationsthat the imperatives in the CEE process are often administrative and diplomaticrather than environmental and that notwithstanding the international scrutiny of draftCEEs, state action may not be significantly changed. Suggestions are made on improvementsto the CEE process. The Madrid Protocol is a framework convention, designed sothat its technical annexes, including that addressing EIA, may be periodically updated.